Patent Selections - Bentham Science Publishers (Recent Patents on Biotechnology, 2010)
The patents annotated in this section have been selected from various patent data bases. These recent patents are relevant to the articles published in this journal issue, categorized by different biotechnology methods, process and techniques involved.